Mathematical modelling in tuberculosis transmission and impact on early intervention (chemoprophylaxis) in Malaysia / Nurhuda Ismail ... [et al.] - Ismail, Nurhuda; Awang Mahmud, Awang Bulgiba; Nagelkerke, Nicolaas J. D.; Awang, Omar; Dony, Jiloris F.; Mohd Hashim, Suzana (2011)
Background: Tuberculosis remains as one of the highest unresolved disease burden among re-emerging diseases in Malaysia for the last twenty years. With current treatment protocol emphasizing among the infectives, we seek to find if combination treatment of these active cases with lsoniazid Preventive Therapy for high risk latent tuberculosis infection groups among non-HIV population would give greater impact on reducing incidence.